CRDS of 17O enriched water between 5850 and 6671 cm−1: More than 1000 energy levels of H217O and HD17O newly determined. (July 2016) - Mikhailenko, S.N.; Leshchishina, O.; Karlovets, E.V.; Mondelain, D.; Kassi, S.; Campargue, A.
Abstract: The room temperature absorption spectrum of water vapor highly enriched in 17 O has been recorded by Cavity Ring Down Spectroscopy (CRDS) between 5850 and 6671 cm −1 . Two series of recordings were performed with pressure values of 1.0 and 12.0 Torr. The investigated spectral region corresponds to the important 1.55 μm transparency window of the atmosphere where water absorption is very weak. The high sensitivity of the recordings ( α min 5×10 −11 cm −1 ) allows detecting lines with intensity spanning six orders of magnitude (1.4×10 −30 –3.6×10 −24 cm/molecule at room temperature). The experimental list includes more than 10, 300 lines. The assignments of water lines were performed using known experimental energy levels as well as calculated line lists based on the results of Partridge and Schwenke. More than 8500 lines were assigned to 9619 transitions of six water isotopologues (H2 16 O, H2 17 O, H2 18 O, HD 16 O, HD 17 O and HD 18 O). All but four transitions of the 1 6 O and 18 O isotopologues were assigned using known experimental energy levels. More than half of the assigned H2 17 O and HD 17 O transitions correspond to new (or corrected) upper energy levels. About 1000 new H2 17 O transitions associated with upper states of the second triad and of the ﬁrst hexad were identiﬁed. Most of the newly assigned HD 17 O transitions belong to the ν1 +ν3 and 2ν2 +ν3 bands. The assigned transitions allowed to newly determine or correct 20 highly excited rotational levels of the vibrational ground state of this isotopologue. Overall 791 and 266 energy levels are newly determined for H2 17 O and HD 17 O, respectively. A few additional levels were corrected compared to literature values. The obtained experimental results are compared to the spectroscopic parameters provided by the HITRAN database and to the empirical energy levels recommended by an IUPAC task group. Highlights: The CRDS spectrum of 17 O enriched water vapor is recorded between 5852 and 6667 cm −1 . About 8500 lines were assigned to six water isotopologues. 2511 H2 17 O transitions were assigned and 791 new energy levels were derived. 1534 HD 17 O transitions were assigned and 266 new energy levels were derived. New HD 17 O levels include 15 high rotational levels of the vibrational ground state.